On-Farm Green Manure Cover Crop (GMCC) Intercropping Strategy Trial under Conservation Agriculture - International Maize and Wheat Improvement Center; Zambian Agriculture Research Institute (International Food Policy Research Institute, 2019)
This study contains data originated from on-farm trials that were conducted to provide viable options to smallholder farmers to improve soil fertility and human nutrition, to increase biomass for fodder and groundcover and to enhance the resilience of current farming systems against the negative effects of climate variability and change. Green manures or cover crop were used as the option. The trials were conducted at farms in Chipata and Lundazi districts of the eastern province of Zambia. The following treatments were used for the trial: - Sole cropping maize; - Maize ? Pigeonpea intercropping; - Maize ? Pigeonpea intercropping with 60-day cowpea; - Maize ? Dolichos Lablab intercropping; - Maize/Gliricidia sepium/pigeonpea intercrop (year 1: groundnuts/Gliricidia; Year 2 soybean/pigeonpea/Gliricidia; year 3 - Maize/Pigeonpea/Gliricidia